2020
DOI: 10.1016/j.cct.2019.105920
|View full text |Cite
|
Sign up to set email alerts
|

Patient randomized trial of a targeted navigation program to improve rates of follow-up colonoscopy in community health centers

Abstract: Background: Colorectal cancer (CRC) screening by annual fecal immunochemical test (FIT) is an accessible and cost-effective strategy to lower CRC incidence and mortality. However, this mode of screening depends on follow-up colonoscopy after a positive FIT result. Unfortunately, nearly one-half of FIT-positive patients fail to complete this essential screening component. Patient navigation may improve follow-up colonoscopy adherence. To deliver patient navigation costeffectively, health centers could target na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These supports are particularly needed for patients aged 65 and older, those who lack health insurance, and those who have not attended a clinic visit in the year prior to an abnormal FIT result. Prediction modeling could be useful to further identify patients who may benefit most from such supports [ 15 ]. Moreover, our findings show that while fewer than half of patients with an abnormal FIT completed a colonoscopy, time to colonoscopy completion overall was within the timeframe of national benchmarks, possibly suggesting an absence of prolonged scheduling delays among those who successfully access care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These supports are particularly needed for patients aged 65 and older, those who lack health insurance, and those who have not attended a clinic visit in the year prior to an abnormal FIT result. Prediction modeling could be useful to further identify patients who may benefit most from such supports [ 15 ]. Moreover, our findings show that while fewer than half of patients with an abnormal FIT completed a colonoscopy, time to colonoscopy completion overall was within the timeframe of national benchmarks, possibly suggesting an absence of prolonged scheduling delays among those who successfully access care.…”
Section: Discussionmentioning
confidence: 99%
“…The PRECISE study is an individual randomized controlled trial of patient navigation versus usual care for follow-up colonoscopy completion among patients who receive an abnormal FIT result at Sea Mar Community Health Centers [ 15 ]. As part of PRECISE, we conducted a baseline assessment of follow-up colonoscopy in a retrospective cohort of patients who had an abnormal FIT result over a one-year interval from August 5, 2017, to August 4, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The study is a collaborative partnership between the Oregon Health & Science University’s Oregon Rural Practice-based Research Network and the Kaiser Permanente Northwest Center for Health Research. Study activities build on prior mailed FIT and patient navigation implementation research conducted by our team [ 32 44 ], best practices identified at a Centers for Disease Control Mailed FIT Summit [ 45 ], rural cancer control recommendations by rural health experts [ 46 ], participatory implementation science principles [ 47 ], and formative research conducted by the Community Health Advocacy and Research Alliance [ 31 , 48 – 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our mailed FIT outreach program uses a collaborative clinic-health plan-vendor model designed and pilot-tested by our team as part of the BeneFIT study [ 56 ] and adapted for rural regions [ 55 , 56 ]. The patient navigation component uses the New Hampshire Colorectal Cancer Screening Program [ 61 ], with adaptations based on prior implementations by our study team and pilot-testing for rural clinics [ 44 , 62 ]. The implementation of the multi-component program is supported by workflow mapping, formal training, and ongoing implementation support provided by practice facilitators and other members of the research team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation